Agrometeorological models for groundnut crop yield forecasting in the Jaboticabal, Sao Paulo State region, Brazil - Moreto, Victor Brunini [UNESP]; Rolim, Glauco de Souza [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2015)
Forecast is the act of estimating a future event based on current data. Ten-day period (TDP) meteorological data were used for modeling: mean air temperature, precipitation and water balance components (water deficit (DEF) and surplus (EXC) and soil water storage (SWS)). Meteorological and yield data from 1990-2004 were used for calibration, and 2005-2010 were used for testing. First step was the selection of variables via correlation analysis to determine which TDP and climatic variables have more influence on the crop yield. The selected variables were used to construct models by multiple linear regression, using a stepwise backwards process. Among all analyzed models, the following was notable: Yield = -4.964 x [SWS of 2 degrees TDP of December of the previous year (OPY)] - 1.123 x [SWS of 2 degrees TDP of November OPY] + 0.949 x [EXC of 1 degrees TDP of February of the productive year (PY)] + 2.5 x [SWS of 2 degrees TDP of February OPY] + 19.125 x [EXC of 1 degrees TDP of May OPY] - 3.113 x [EXC of 3 degrees TDP of January OPY] + 1.469 x [EXC of 3 TDP of January of PY] + 3920.526, with MAPE = 5.22%, R-2 = 0.58 and RMSEs = 111.03 kg ha(-1).
Keywords: crop model; water balance; prediction; production